Type 1 diabetes diagnosed during pregnancy—an unusual but important challenge: a case series and review of literature - Caretto, Amelia; Pedone, Erika; Laurenzi, Andrea; Bolamperti, Filippo; Cellai, Caterina; Pasi, Federica; Girardelli, Serena; Castiglioni, Maria Teresa; Dozio, Nicoletta; Scavini, Marina (Frontiers in Medicine, 2025)
Hyperglycemia diagnosed during pregnancy is most commonly due to gestational diabetes mellitus (GDM), while a minority of cases are attributable to previously unrecognized type 2 diabetes mellitus (T2DM) or, more rarely, type 1 diabetes mellitus (T1DM). Although T1DM has traditionally been associated with onset during childhood or adolescence, recent evidence shows that nearly 40% of new T1DM cases occur after the age of 30 years, coinciding with the age at which many women in Europe begin pregnancy. This highlights the importance of considering T1DM in the differential diagnosis of hyperglycemia during pregnancy, given the relevant implications for the management and outcomes of these pregnancies. Diabetes-related autoantibodies have been detected in pregnancies complicated by GDM, with prevalence varying widely (from less than 1% to up to 18%), depending on population risk, assay, and antibody type. The most commonly detected autoantibodies in GDM are islet cell antibodies (ICA) and anti-glutamic acid decarboxylase antibodies (GADA), while the presence of multiple autoantibodies is much rarer. Women with hyperglycemia and diabetes-related autoimmunity display a peculiar clinical profile: they usually have a normal pre-pregnancy BMI, low insulin resistance, and require insulin therapy more often than antibody-negative patients with hyperglycemia. They are typically younger and are likely to have a family history of diabetes or other autoimmune diseases. Importantly, the presence, and especially the number, of positive autoantibodies is associated with an increased risk of progression to T1DM after pregnancy. Therefore, identifying autoimmune markers of beta-cell damage in pregnant women with hyperglycemia is critical for prognosis, tailored management, and appropriate follow-up.